2009
DOI: 10.1080/09670260802710269
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and microspectrophotometric characterization of multiple species of cyanobacterial photosymbionts coexisting in the colonial ascidianTrididemnum clinides(Tunicata, Ascidiacea, Didemnidae)

Abstract: Trididemnum clinides is a multi-photosymbiotic ascidian that inhabits shallow coral reef lagoons. Three types of cyanobacteria are harboured in the tunic of the ascidian colony; of these, two are unicellular coccoid cyanobacteria and the other is a multicellular filamentous type. They also differ in ultrastructure and distribution patterns within the host tunic. Microspectrophotometric analysis revealed the composition of photosynthetic pigments in each photosymbiont. One of the coccoid types is yellowish-gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
(42 reference statements)
0
22
0
Order By: Relevance
“…Calothrix was also identified by Sanger sequencing of 16S PCR clone libraries. Filamentous cyanobacteria have previously been observed in Prochloron-bearing didemnids on several occasions, but not from L. patella (23)(24)(25)(26)(27)(28)(29). A few eukaryotic microbes, such as diatoms and dinoflagellates, were observed in L2 but not in L1 (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Calothrix was also identified by Sanger sequencing of 16S PCR clone libraries. Filamentous cyanobacteria have previously been observed in Prochloron-bearing didemnids on several occasions, but not from L. patella (23)(24)(25)(26)(27)(28)(29). A few eukaryotic microbes, such as diatoms and dinoflagellates, were observed in L2 but not in L1 (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…P. didemni thus allows didemnid ascidians to thrive in nutrient-poor, light-rich environments of the tropics. Didemnids have also been found to contain other types of microbes, but unlike P. didemni, without extensive in vivo functional studies (21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…The slower dynamics of O 2 in this layer is probably the result of light screening by cyanobacteria in the upper test and the Prochloron layer. Both zones of cyanobacteria have been observed before and the tunic is known to harbor the cyanobacterium Synechocystis trididemni and other cyanobacteria with special pigmentation (Lafargue and Duclaux, 1979; Kott, 1984; Cox et al, 1985; Hirose et al, 2009b; López-Legentil et al, 2011). López-Legentil et al (2011) found Chl d -containing Acaryochloris cells in the unic of other didemnid ascidians on mangrove roots in the Bahamas but we have not found any evidence for Chl d in the unic of L .…”
Section: Discussionmentioning
confidence: 99%
“…These mostly include other cyanobacteria, 32-36 but also reports about other types of bacteria, especially proteobacteria. 37-40 In the course of sequencing the P. didemni genome, we obtained an immense amount of data concerning other bacteria as well.…”
Section: Didemnid Houses For Bacteriamentioning
confidence: 99%